Melbourne Main Sewer Project – Construction Phase – Soft Ground Tunnelling in the Yarra Delta - P Clark (The Australasian Institute of Mining and Metallurgy, 2011)
This paper discusses the challenges, solutions and lessons learnt as tunnelling work continues on the Melbourne Main Sewer Replacement (MMSR) project.The MMSR project is a $220 million dollar project for the Melbourne Water Corporation. It involves the construction of approximately 4.2 km of new sewer from the southern fringe of the CBD through the inner metropolitan suburbs of Port Melbourne and South Melbourne.Of the 4.2 km of sewer currently in construction approximately 2.2 km will be constructed using a 2.95 m diameter Lovat EPB tunnel boring machine (TBM) with approximately 1.9 km of small diameter (300 to 600 mm) reticulation sewers constructed using trenchless techniques.These sewers are being constructed in a dense urban environment, which means that the tunnels and shafts are often in close proximity to buildings and structures. The underground constructionof the sewer is further complicated by the variable geology of the ancient Yarra River delta which includes weathered basalts, the infamous Coode island silt formation and fine loose sands.Some of the key challenges and lessons learnt so far during construction include:· steering and alignment control of the TBM through very soft silt with little residual strength,· development and refinement of a monitoring and alarm system for leaving the machine dormant on a day works only project,· control and measurement of tunnel lining defl ection during ring build and grouting,· prediction and monitoring of surface settlements during tunnel excavation,· improved understanding of the geology and hydrogeology at this previously unchartered area of Melbourne,· consolidation settlement due to dewatering at shafts required careful construction controls, and· ground support and excavation in close proximity to the existing 110 year old sewer which requiredvery detailed risk control measures.